(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
This paper shares the remains of extraordinary wooden furniture covered in ivory relief decorations. The discovery was made during the new works (July 2007-Spring 2009) for the excavation, conservation and enhancement of the area of the Villa of the Papyri carried out by the Superintendency and financed by the European Community within its Regional Operative Program (P.O.R.) for the Campania Region.The exceptional nature of this discovery lies particularly in the high quality materials used and the intricacy of the relief decoration, full of religious symbolism prevalently used in connection to Dionysius.